Macroeconomics : A European Perspective - Blanchard, Olivier (Pearson International Content, 2021)
Develop a unified view of the latest global macroeconomic events, connecting the short, medium and long run    Macroeconomics: A European Perspective, 4th edition, by Blanchard, Amighini & Giavazzi is based on the best-selling US text by Blanchard and presents an integrated, global view of macroeconomics, showing the connections between goods markets, financial markets, and labour markets worldwide.     This is a book rooted in the real-world: from the major economic crisis of the late 2000s to the profound economic effects caused by the COVID-19 pandemic, from monetary policy in the US, to Brexit, the problems of the Euro area and growth in China, it will help you make sense not only of current macroeconomic events but also those that may unfold in the future.    This is an essential text for students studying Macroeconomics at intermediate level, fully supported by  MyLab Economics.       Reach every student by pairing this text with MyLab Economics  “MyLab™ is the teaching and learning platform that empowers you to reach every student. By combining trusted author content with digital tools and a flexible platform, MyLab personalizes the learning experience and improves results for each student.     Pearson, the world’s learning company.